Black esophagus with concomitant candidiasis developed after diabetic ketoacidosis - Kim, Yong Hwan (Baishideng Publishing Group Inc, 2007)
Black esophagus is a very rare disease and its pathogenesis has been unclear. Black esophagus developed concomitantly with candidiasis after diabetic ketoacidosis has not been reported yet. We report a case who developed esophageal stricture after the treatment of black esophagus and thus balloon dilatation was performed several times but failed, hence, surgical treatment was performed.